Genetic differentiation of the G6/7 cluster of Echinococcus canadensis based on mitochondrial marker genes. Issue 14 (December 2017) - Addy, Francis; Wassermann, Marion; Kagendo, Dorothy; Ebi, Dennis; Zeyhle, Eberhard; Elmahdi, Ibrahim E.; Umhang, Gerald; Casulli, Adriano; Harandi, Majid F.; Aschenborn, Ortwin; Kern, Peter; Mackenstedt, Ute; et al.
Graphical abstract: Highlights: The cluster G6/7 is a genotypic entity, distinct from G8 and G10, of Echinococcus canadensis . Echinococcus canadensis G6/7 microdiversity revealed 73 mt cox1-nad1 concatenated haplotypes. Echinococcus canadensis G6/7 haplotype grouping is region- and/or host-dependent. Ancestral polymorphism and haplotypes of E. canadensis G6/7 were seen in sub-populations. Abstract: Among the genotype/species causing cystic echinococcosis, the taxonomic status of Echinococcus canadensis is only partially resolved. Within E. canadensis, four genotypes (G6, G7, G8 and G10) have been described based on short mitochondrial sequences, of which G6 and G7 (the 'camel' and the 'pig' strain, respectively) are closely related and variously regarded as microvariants of a single strain G6/7. Globally, this G6/7 cluster is the second most important agent of human cystic echinococcosis and is the predominant Echinococcus taxon in large parts of sub-Saharan Africa. To add data on the internal structure and the geographical distribution of this cluster, we analysed diversity and population structure of 296 isolates of E. canadensis from sub-Saharan Africa, the Middle East and Europe using the complete mitochondrial cytochrome c oxidase subunit 1 ( cox1 ) (1, 608 bp) and NADH dehydrogenase subunit 1 ( nad1 ) (894 bp) gene sequences. Polymorphism of the mtDNA loci gave 51 ( cox1 ), 33 ( nad1 ) and 73 ( cox1 - nad1 concatenated) haplotypes. African and Middle Eastern isolates mainly grouped in a star-like structure around a predominant haplotype, while the European isolates produced more diversified networks. Although the cox1 diagnostic sequence for G6 is frequent in the African/Middle Eastern sub-cluster, and that for G7 is common in the European isolates, numerous intermediate variants prevent a clear distinction into 'G6' or 'G7', and the entire taxon is best treated as a common haplotype cluster G6/7. Meanwhile, the G6/7 cluster is clearly distinct from sequences of wildlife isolates of G8 and G10 from the northern hemisphere, and sequences of the latter genotypes were remarkably distant from each other. It is clear from the present study that, based on mitochondrial data, G6/7 is a coherent genotypic entity within E. canadensis that retains substantial intraspecific variance, and sub-populations share common ancestral polymorphisms and haplotypes. This study provides the basis for wider biogeographic comparison and population genetics studies of this taxon.